Irregular Pulse and Cardiovascular Disease From NHANES (1999–2018): A Cross‐Sectional Study - Qingping Zeng; Weihong Chang; Rui Zhang; Hongxuan Fan; Aman Liu; Ping Zhang; Fei She; Boda Zhou (Health Science Reports)
ABSTRACT Background and Aims Pulse is an easily accessible life sign, while irregular pulse could be easily detected in daily life during blood pressure test. However, whether irregular pulse was associated with cardiovascular disease (CVD) or mortality has not been reported on a large population scale. Here, we investigated the association between irregular pulse, CVD, and CVD mortality, to explore the potential of irregular pulse as screening indicator for CVD and mortality, thus influencing health policy. Methods This cohort study used National Health and Nutrition Examination Survey data from 1999 through 2018 and linked mortality information until 2019. Eligible participants were adults with valid records of self‐report CVD and pulse characteristics. Results We included data from 49,681 participants in the analysis. Compared with regular pulse group, irregular pulse group demonstrated an increased risk of CVD (1.34, [1.14, 1.58]), especially heart failure (1.75, [1.37, 2.24]) and coronary heart disease (1.27, [1.01, 1.60]). Irregular pulse group showed an increased risk for all‐cause mortality (HR 1.29, [95% CI, 1.17–1.42]) and CVD mortality (HR 1.53, [95% CI, 1.30–1.81]) compared with regular pulse group. The findings suggest that irregular pulse was associated with CVD and mortality. Participants with irregular pulse were associated with a significantly increased risk of all‐cause mortality (HR 1.29, 95% CI [1.17, 1.42], p < 0.001), and CVD mortality (HR 1.53, [1.30, 1.81], p < 0.001). Conclusion Our study found that people with irregular pulse have a higher incidence of cardiovascular disease and cardiovascular disease mortality than people with regular pulse. These findings highlight the importance of health screening and risk management for people with irregular pulse.